The Development of Local Human Capital Curriculum on Processing Organic Rice for Ban Nonrang Wittayakarn School Students with Community Participation - Sitasuta, Sompit (Suan Dusit Graduate School Academic Journal, 2023)
The objectives of this study were: 1) to develop a local human capital curriculum on processing organic rice for Ban Nonrang Wittayakarn school students with community participation, and 2) to study the effectiveness of a local human capital curriculum on processing organic rice for Ban Nonrang Wittayakarn school students with community participation. The participatory action research was undertaken in this study. The target groups used in the research were divided into two groups; group 1 included administrators, parents, the chairman of the organic rice processing community enterprise group, local scholars, local organization representatives and group 2 included those involved in the teaching and learning process of Ban Nonrang Wittayakarn school. The sample were recruited by using purposive sampling. An Interview form, curriculum requirement questionnaires, pre and post learning test, work-product, work-performance and satisfaction assessment forms were used for collecting data. The quantitative data was analyzed through frequency and percentage, while the qualitative data was analyzed by using content analysis. The research results revealed that: (1) the local human capital curriculum on processing organic rice for Ban Nonrang Wittayakarn school students with community participation and collaboration was in accordance with the students’ needs and interests. The curriculum helped promote local resources to create added value for self and family and actually use resources for future careers. The overall evaluation of the needs for curriculum development was at the high level with the average of 4.79) and (2) The students' satisfaction with the said curriculum after the curriculum had been tried out was at the very high level with the average of 4.62.